Camarillo State Hospital Treatment Division diagram - F.H. Garrett:::::: (1959)
A map diagram of the Camarillo State Hospital "Treatment Division" created on October 26, 1959. The map displays a visual of the Camarillo State Hospital in which different areas of the hospital are shown with a label of what each functions for. For example there are departments in the hospital which focus on psychology, social services, and rehabilitation all being their own department.